MAKING EARLY WARNING PROCEDURE OF CRISIS CONTRACT - Anugerah Perkasa Baboe (Lambung Mangkurat University Press, 2012)
One of the problems that occurs on projects in the areas of Highways Department of Public Works in Kapuas is the delay in project completion. Some projects even have a critical condition. This is due to the fact that resource needs of the project are not met. In fact, the data submitted by the contractors during the tender procees are actually sufficienty good. However, at the time of execution, some of the projects undertaken by the contractors, the winning bidder, undergo a critical conditions. Therefore, in order to prevent future projects from leading to a critical state, it is important to introduce an instrument of early warning procedure (early warning) as a useful input for decision makers.The goal of this research is to make a system of early warning for critical control conditions (pro-konkrit) so that future projects can be controlled and prevented from getting into critical conditions. This research was limited to the use of equipment, labor and money as well as the management contractor. The system is proposed to be used before the contract is signed. The system is expected to be an input for decision makers.The result of this study is a system that consists of components of the resources (including: tools, labor and capital), management components (including: data and information, work procedures, monitoring and action), component of the project (such as: employment data, components of the evaluator, and component output (critical/non critical). The results of testing the feasibility and value of users about the system of contract crisis procedure that gives an accurate information, easy to use, the user understand the output of system contract crisis procedure and the contract crisis procedure gives the advantage for users.